2014
DOI: 10.1016/j.neuropharm.2014.05.042
|View full text |Cite
|
Sign up to set email alerts
|

SKF-83959 is not a highly-biased functionally selective D1 dopamine receptor ligand with activity at phospholipase C

Abstract: SKF-83959 [6-chloro-7,8-dihydroxy-3-methyl-1-(3-methylphenyl)-2,3,4,5-tetrahydro-1H-3-benzazepine] is reported to be a functionally selective dopamine D1 receptor ligand with high bias for D1-mediated phospholipase C (PLC) versus D1-coupled adenylate cyclase signaling. This signaling bias is proposed to explain behavioral activity in both rat and primate Parkinson’s disease models, and a D1-D2 heterodimer has been proposed as the underlying mechanism. We have conducted an in-depth pharmacological characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 74 publications
2
47
1
Order By: Relevance
“…In some cases, the published data actually agree with the findings of Lee et al (2014). For example, Gnanalingham et al (1995b) reported that SKF-83959 did not cause significant stimulation of adenylate cyclase, yet their data clearly show measurable (∼50%) intrinsic activity, with some data points marked as significant.…”
Section: Hypothesis: Skf-83959 Has No Intrinsic Activity At D 1 -Medisupporting
confidence: 61%
See 4 more Smart Citations
“…In some cases, the published data actually agree with the findings of Lee et al (2014). For example, Gnanalingham et al (1995b) reported that SKF-83959 did not cause significant stimulation of adenylate cyclase, yet their data clearly show measurable (∼50%) intrinsic activity, with some data points marked as significant.…”
Section: Hypothesis: Skf-83959 Has No Intrinsic Activity At D 1 -Medisupporting
confidence: 61%
“…and with similar potency as seen with adenylate cyclase activation (Lee et al, 2014). Importantly, its potency in both D 1 -mediated adenylate cyclase and b-arrestin assays was in the nanomolar range, similar to its affinity (Lee et al, 2014).…”
Section: Hypothesis: Skf-83959 Has No Intrinsic Activity At D 1 -Medimentioning
confidence: 54%
See 3 more Smart Citations